Diels-Alder reactivity of triisopropylsilyl ethynyl substituted acenes [data] - Jester, Fabian; Kaczun, Tobias; Maier, Steffen; Meiners, Paul; Weigold, Svenja; Rominger, Frank; Dreuw, Andreas; Freudenberg, Jan; Bunz, Uwe H. F. (Universität, 2024)
We investigated the Diels-Alder reaction of 6,13-bis(triisopropylsilyl)pentacene (1) with small dienophiles such as (bridged) dihydronaphthalenes/cyclohexenes that yielded adducts at the central ring, the other dienophiles predominantly or exclusively attacked the unsubstituted off-center ring. The difference in regioselectivity was investigated by DFT calculations. Apart from dispersion interactions, it is due to the steric demand of the dienophiles, which need to fit in between the silylethynyl substituents to react at the central ring. Epoxynaphthalene adducts of 1 as well as its anthracene and tetracene congeners were deoxygenated, easily furnishing triarenobarrelenes with TIPS-ethynyl substituents at the bridge heads, attractive building blocks for porous solids and higher acene-based trimers.
Gefördert durch: Deutsche Forschungsgemeinschaft (SFB): 1249, Deutsche Forschungsgemeinschaft: INST 40/575-1 FUGG, Deutsche Forschungsgemeinschaft: INST 35/1596-1 FUGG
Gesehen am 13.03.2025
Keywords: Forschungsdaten; Datenbank